An electroanalytical application of 2-aminothiazole-modified silica gel after adsorption and separation of Hg(II) from heavy metals in aqueous solution - Dias Filho, Newton L.; do Carmo, Devaney R.; Rosa, Andre H. (Elsevier B.V., 2006)
2-Aminothiazole covalently attached to a silica gel surface was prepared in order to obtain an adsorbent for Hg(II) ions having the following characteristics: good sorption capacity, chemical stability under conditions of use, and, especially, high selectivity. The accumulation voltammetry of mercury(II) was investigated at a carbon paste electrode chemically modified with silica gel functionalized with 2-aminothiazole (SIAMT-CPE). The repetitive cyclic voltammogram of mercury(II) solution in the potential range -0.2 to + 0.6 V versus Ag/AgCl (0.02 mol L-1 KNO3; V = 20 mV s(-1)) show two peaks one at about 0.1 V and other at 0.205 V. The anodic wave peak at 0.205 V is well defined and does not change during the cycles and it was therefore further investigated for analytical purposes using differential pulse anodic stripping voltammetry in differents supporting electrolytes. The mercury response was evaluated with respect to pH, electrode composition, preconcentration time, mercury concentration, cleaning solution, possible interferences and other variables. The precision for six determinations (n = 6) of 0.02 and 0.20 mg L-1 Hg(II) was 4.1 and 3.5% (relative standard deviation), respectively. The detection limit was estimated as 0.10 mu g L-1 mercury(II) by means of 3:1 current-to-noise ratio in connection with the optimization of the various parameters involved and using the highest-possible analyser sensitivity. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: silica gel modified; preconcentration; heavy metals; carbon paste electrodes